Development of Silicone-Coated Hydrophobic Deep Eutectic Solvent-Based Membranes for Pervaporation of Biobutanol - Zuniga-Navarro, G; Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C (Elsevier B.V., 2021)
Hydrophobic Deep Eutectic Solvents (HDES) are considered a relatively novel class of solvents, which show perfect features to incorporate them in pervaporation membranes. Composite HDES membranes offer a separation media, which shows a faster molecular diffusion than polymeric membranes, combining the best properties of liquid and polymer membranes, such a high selectivity with high burst pressure and durability. In this work, the separation of acetone–butanol–ethanol mixtures (ABE) from aqueous solutions, is carried out by pervaporation using membranes prepared with HDES lidocaine-thymol (Lidol) and CH3(CH2)8COOH-Thymol (Decadol), coated with two polydimethylsiloxane (PDMS) flat sheet membranes. The composite membranes showed improved results for the butanol/water selectivity compared to the single PDMS layer membrane used as a control. The total flux of butanol obtained with the Lidol-based membrane was 2.93 × 10−3 [kg m−2 hr−1]. The total flux of water was 1.22 × 10−4 [kg m−2 hr−1], showing a selectivity value for butanol/water of 1932, while the control membrane had a selectivity value of 6. The results obtained with the composite membranes exhibited a higher and more stable performance in separating butanol from the ABE solution. The improvement in the selectivity can be explained by the synergic effect of the PDMS coating with the HDES layer. © 2021 Elsevier B.V.